Antimicrobial resistance: The next probable pandemic - Krishnapriya U (Open Journal of Bacteriology - Peertechz Publications, 2022)
Even as the world continues to grieve for those lost to the SARS-CoV-2 pandemic, another pandemic is brewing that has the potential to kill hundreds of millions of people in a century or less. In the far future, patients' lives are being cut short in hospital wards by the stealthy but widespread epidemic of antimicrobial resistance. Unfortunately, the global health community is now confronting the silently growing pandemic that could threaten some of the most significant advancements in contemporary medicine. Considering that current medical professionals will eventually pass the torch to their students, who will hopefully lead to further improvements in antimicrobial resistance and antibiotic usage, medical students have the opportunity to contribute to a long-term solution to this problem. Future medical professionals, then, need to be better equipped to make prudent and economical use of antimicrobials.